Pelaksanaan Peraturan Gubernur Bali Nomor 97 Tahun 2018 Tentang Pemakaian Kantong Plastik Sekali Pakai di Kota Denpasar - Gede Putu Oka Brahma Adhi; I Wayan Rideng; Ida Ayu Putu Widiati (Jurnal Interpretasi Hukum, 2021)
The community and the Government of Denpasar City took the initiative to save Bali Island, which is known as the last paradise island, "The Last Island Paradise" with the hope of having an impact on preserving the universe. Public reactions to the issuance of Regional Regulation Number 97 of 2018 are very diverse. There are those who agree and then provide support with the real action not to use plastic-based containers. The purpose of this study is to reveal the inhibiting factors for the implementation of Bali Governor Regulation Number 97 of 2018 against the restriction of single-use plastic bags in Denpasar City and the impact of implementing Bali Governor Regulation Number 97 of 2018 on Tourism Development in Denpasar City. The type of research used in this research is empirical law research. Based on the research that has been done, it is an inhibiting factor for the implementation of Governor Regulation Number 97 of 2018 concerning Reducing the Use of Plastic Bags, among others: lack of public awareness, lack of facilities to manage waste, the culture of the community using plastic bags is still high, law enforcement of Denpasar Mayor Regulation Number 36 of 2018 is still weak.